Sliding Mode Control of the Fractional-Order Unified Chaotic System - Jian Yuan; Bao Shi; Xiaoyun Zeng; Wenqiang Ji; Tetie Pan (Abstract and Applied Analysis)
This paper deals with robust synchronization of the fractional-order unified chaotic systems. Firstly, control design for synchronization of nominal systems is proposed via fractional sliding mode technique. Then, systematic uncertainties and external disturbances are considered in the fractional-order unified chaotic systems, and adaptive sliding mode control is designed for the synchronization issue. Finally, numerical simulations are carried out to verify the effectiveness of the two proposed control techniques.